Triple Helix Collaboration to Address Increasing Financial Cybercrime - Firdausi, Iasa Nur; Nirawati, Lia (Jurnal Bisnis Indonesia, 2024)
Cybercrime or what is commonly known as cybercrime is a series of criminal activities that useinformation technology, networks or computers as the main tool or target. In responding to anddealing with the increasing number of cybercrimes in the financial sector, both universities, industryand government have interrelated influences and cannot act alone. A qualitative descriptive approachwas carried out in this research by discussing various issues in society and providing solutions oralternatives through collaboration carried out by the triple helix in a systematic and comprehensivemanner. Universities act as institutions in charge of education and basic research, industry plays arole in creating commercial goods that support programs, government acts as a supervisor andregulates the market. Universities need to increase the scale of outreach and education regardingbetter alternatives to online gambling. Companies as service providers are also required to providemore varied and innovative services to prevent people from being caught in cybercrimes such asonline gambling, illegal online loans and fraudulent investments. The government must also takeaction in the form of repressive measures such as strengthening existing regulations.Keywords: Cyber Crime; Triple Helix; Online Gambling; Illegal Online Loans; FraudulentInvestment